2008
DOI: 10.1016/j.molcel.2008.04.027
|View full text |Cite
|
Sign up to set email alerts
|

mTOR-Raptor Binds and Activates SGK1 to Regulate p27 Phosphorylation

Abstract: The cell-cycle effects of mTORC1 are not fully understood. We provide evidence that mTOR-raptor phosphorylates SGK1 to modulate p27 function. Cellular mTOR activation, by refeeding of amino acid-deprived cells or by TSC2 shRNA, activated SGK1 and p27 phosphorylation at T157, and both were inhibited by short-term rapamycin treatment and by SGK1 shRNA. mTOR overexpression activated both Akt and SGK1, causing TGF-beta resistance through impaired nuclear import and cytoplasmic accumulation of p27. Rapamycin or rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
211
5
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(224 citation statements)
references
References 70 publications
7
211
5
1
Order By: Relevance
“…A previous report indicates that mTORC1 regulates p27 by activating serum-and glucocorticoidinducible kinase 1 (SGK1) (Hong et al, 2008), although a recent study showed that mTORC2, rather than mTORC1, is responsible for SGK1 activation (GarciaMartinez and Alessi, 2008). Our work cannot conciliate the differences between these two reports, but indicates that mTORC1 is not involved in regulating p27 in Tsc2-null cells.…”
Section: Discussionmentioning
confidence: 99%
“…A previous report indicates that mTORC1 regulates p27 by activating serum-and glucocorticoidinducible kinase 1 (SGK1) (Hong et al, 2008), although a recent study showed that mTORC2, rather than mTORC1, is responsible for SGK1 activation (GarciaMartinez and Alessi, 2008). Our work cannot conciliate the differences between these two reports, but indicates that mTORC1 is not involved in regulating p27 in Tsc2-null cells.…”
Section: Discussionmentioning
confidence: 99%
“…These observations include: (a) mTOR is an atypical serine/ threonine kinase; (b) there are two mTOR complexes, mTORC1 and mTORC2; (c) mTORC1 and mTORC2 have different targets and varied sensitivity to rapamycin; (d) mTOR functions downstream of growth factor receptors; (e) inhibition of mTORC1 may paradoxically leads to Akt and ERK phosphorylation; and (f) mTORC2 is the hydrophobic motif kinase for Akt and SGK1 [6,32].…”
Section: Discussionmentioning
confidence: 99%
“…[105][106][107] In a cell line overexpressing mTOR, however, SGK was phosphorylated by mTORC1, and subsequently blocked cell cycle arrest. 108 In contrast to the mTORC2 substrate PKCa, PKCd is phosphorylated by mTORC1, phosphorylates 4E-BP1, and controls the initiation of translation. 104 Interestingly, PKCd is a kinase for the transcription factor STAT1 kinase, and was detected in a rapamycin-sensitive macromolecular complex with mTOR and STAT1.…”
Section: Translation and Cell Growthmentioning
confidence: 99%